ANGKA CAKUPAN K1 IBU HAMIL PERIODE BULAN JULI 2015 â JUNI 2016 DI POLINDES DESA KEPUHANYAR KECAMATANMOJOANYARÂ KABUPATENMOJOKERTO - MaÃ¢Â€Â™rifah, Asirotul; Hafidah, Nur (JURNAL KEPERAWATAN SEHAT, 2016)
Every expectant mother is expectedtorun a healthy pregnancy, childbirth safely and give birth to a healthy baby. Therefore, every pregnant woman should be able to easily access a health facility to obtain appropriate care standards, including the detection of possible problems / diseases that can negative lyimpactthe health of the mother and fetus. The purpose of this study was to determine the numbers K1 coverage among pregnan two menin the village Polindes Kepuhanyar Mojoanyar District of Mojokerto. Design of this research using descriptive method. Population in this researchis data of all pregnan two men who do K1 in July 2015 - June 2016 in the village Polindes Kepuhanyar Mojoanyar District of Mojokerto which amounted to 79 respondents. Sample of 79 respondents were taken using total sampling. Secondary data sources, data collection equipment checklist sheet. Data were analyzed using frequency distribution percentages. The results showed that nearly all respondents made the first visit (K1) of lessthan 12 weeks of gestationalage as many as 64 respondents (81%). However, the government set a target coverageis 95%, so the cover age number of K1 in Polindes Village Kepuhanyar Mojoanyar District of Mojokerto regency period July 2015 - June 2016 declared not meet government targets. The results showed that the coverage K1 place high enough research but did not meet the governmentstargets of 95%. It is influenced by many factors both individual pregnant women, pregnant women and individuals outside of it self. Promotive of the K1 can be performed at various events such as neighbor hood health center, or involving cadres in the respective RT toen courage maternal antenatal mothers especially young gestation.Keywords: K1, Pregnant Women